Development and Validation of SafeHIT: An Instrument to Assess the Self-Reported Safe Use of Health Information Technology - Salahuddin, Lizawati; Ismail, Zuraini; Abdul Rahim, Fiza; Anawar, Syarulnaziah; Hashim, Ummi Rabaah (Applied Clinical Informatics, 2023)
Background Implementing health information technology (HIT) may cause unintended consequences and safety risks when incorrectly designed and used. Yet, the tools to assess self-reported safe use of HIT are not well established.Objective This study aims to develop and validate SafeHIT, an instrument to assess self-reported safe use of HIT among health care practitioners.Methods Systematic literature review and a semistructured interview with 31 experts were adopted to generate SafeHIT instrument items. In total, 450 physicians from various departments at three Malaysian public hospitals participated in the questionnaire survey to validate SafeHIT. Exploratory factor analysis and confirmatory factor analysis (CFA) were undertaken to explore the items that best represent a specific construct and to confirm the reliability and validity of the SafeHIT, respectively.Results The final SafeHIT consisted of 14 constructs and 58 items in total. The result of the CFA confirmed that all constructs demonstrated adequate convergent and discriminant validity.Conclusion A reliable and valid theoretically underpinned measure of determinants of safe HIT use behavior has been developed. Understanding external factors that influence safe HIT use is useful for developing targeted interventions that favor the quality and safety of health care.
Keywords: health information technology; safety; adoption; questionnaire survey; quantitative instrument